Well-differentiated angiosarcoma of spleen: a teaching case mimicking hemagioma and cytogenetic analysis with array comparative genomic hybridization - Xu, Lichen (World J Surg Oncol, 2015)
Primary splenic angiosarcoma is extremely rare but aggressive malignant vascular neoplasm. Here, we report a case of vascular tumor in spleen that was initially misinterpreted as hemangioma. Two years after splenectomy, the patient admitted again with aggravated abdomen pain and severe anemia. The magnetic resonance imaging (MRI) scan showed widely metastases. The ensuing biopsy for lesion both in liver and in bone marrow showed the similar pathological findings as that in spleen, which supported the final diagnosis of well-differentiated splenic angiosarcoma with extensive metastases. The patient was dead in 3 months after discharge without chemotherapy. The copy number changes for spleen lesion detected by array comparative genome hybridization showed copy number gain at 11q23.2, 11q24.3, 12q24.33, 13q34, copy number loss at 1q24.2-q31.3, 1q41-q42.2, 1 q42.3-q43, 2q36.3-q37.3, 2q37.7, 3q13.33-q26.2, 3q28 - q29, 9p11.2, 13q11, 15q11, homozygous copy loss at 8p11.22, 22q11.23. Less than 200 cases of splenic angiosarcoma have been published in literature of English. To the best of our knowledge, this is the first time analyzed cytogenetic alteration in a well-differentiated primary splenic angiosarcoma.